2009
DOI: 10.3858/emm.2009.41.2.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression analyses of human cleft palate tissue suggest a role for osteopontin and immune related factors in palatal development

Abstract: Cleft lip and/or palate (CL/P) is a common congenital malformation with a complex etiology which is not fully elucidated yet. Epidemiological studies point to different etiologies in the cleft lip and palate subgroups, isolated cleft lip (CL), isolated cleft palate (CP) and combined cleft lip and palate (CLP). In order to understand the biological basis in these cleft lip and palate subgroups better we studied the expression profiles in human tissue from patients with CL/P. In each of the CL/P subgroups, sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
1
21
1
5
Order By: Relevance
“…Furthermore, OPN has been emphasized as important for palate formation in recent study on foetal murine palates, which showed significant changes in expression of OPN during craniofacial development [22]. Jakobsen et al by Gene chip analysis and staining with selected antibodies in human embryonic palates found supportive evidence that OPN may play in the development of the normal palate [23]. OPN-positive cell distribution varied from occasional to few positive structures in the patients examined, and OPN expression in the alveolar bone was lower in the CBCLP compared to the control group.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, OPN has been emphasized as important for palate formation in recent study on foetal murine palates, which showed significant changes in expression of OPN during craniofacial development [22]. Jakobsen et al by Gene chip analysis and staining with selected antibodies in human embryonic palates found supportive evidence that OPN may play in the development of the normal palate [23]. OPN-positive cell distribution varied from occasional to few positive structures in the patients examined, and OPN expression in the alveolar bone was lower in the CBCLP compared to the control group.…”
Section: Discussionmentioning
confidence: 94%
“…For example, three of the top 25 CpGs where there is most evidence of differential methylation between CPO and CLO (Table 2) map to two genes that have previously been reported as associated with gestational age and/or age in infancy: NFIX [28,29,61] and SNED1 [29]. However, a previous microarray study of lip tissue found lower expression of NFIX in children with CLP compared to children with CLO even though both groups were sampled at 4-months-old, which provides some evidence that NFIX may be associated with OFCs independently of age [62]. Differences in the surgical protocol for lip and palate repair mean that this limitation (of age differences between children with CPO and CL/P) is likely to be present in other studies of OFCs where samples are collected at surgery, so techniques such as the one described in this paper should be developed to attempt to overcome this.…”
Section: Discussionmentioning
confidence: 99%
“…One study on tissues from CLP of Caucasian origin was obtained for the comparisons between the three types of cleft [10]. During the repair of CLP, the tissue biopsy that was taken out from the patients was found indispensable for genetic analysis.…”
Section: Introductionmentioning
confidence: 99%